A Nanobody‐Conjugated DNA Nanoplatform for Targeted Platinum‐Drug Delivery. (27th August 2019) - Wu, Tiantian; Liu, Jianbing; Liu, Manman; Liu, Shaoli; Zhao, Shuai; Tian, Run; Wei, Dengshuai; Liu, Yangzhong; Zhao, Yao; Xiao, Haihua; Ding, Baoquan
Abstract: The targeted delivery of chemotherapeutic drugs is a major challenge in the clinical treatment of cancer. Herein, we constructed a multifunctional DNA nanoplatform as a versatile carrier of the highly potent platinum‐based DNA intercalator, 56MESS. In our rational design, 56MESS was efficiently loaded into the double‐bundle DNA tetrahedron through intercalation with the DNA duplex. With the integration of a nanobody that both targets and blocks epidermal growth factor receptor (EGFR), the DNA nanocarriers exhibit excellent selectivity for cells with elevated EGFR expression (a common biomarker related to tumor formation) and combined tumor therapy without obvious systemic toxicity. This DNA‐based platinum‐drug delivery system provides a promising strategy for the treatment of tumors. Abstract : Gebündelte Wirkung : Eine Nanoplattform basierend auf einem Doppelbündel‐DNA‐Tetraeder für die gezielte Tumortherapie enthält einen Nanobody, der den auf Tumorzelloberflächen überexprimierten Rezepter des epidermalen Wachstumsfaktors (EGFR) adressiert und blockiert, sowie einen Pt‐basierten DNA‐Interkalator (56MESS).